2023
DOI: 10.3390/jfb14060308
|View full text |Cite
|
Sign up to set email alerts
|

Employing Indirect Adenosine 2A Receptors (A2AR) to Enhance Osseointegration of Titanium Devices: A Pre-Clinical Study

Abstract: The present study aimed to evaluate the effect of dipyridamole, an indirect adenosine 2A receptors (A2AR), on the osseointegration of titanium implants in a large, translational pre-clinical model. Sixty tapered, acid-etched titanium implants, treated with four different coatings ((i) Type I Bovine Collagen (control), (ii) 10 μM dipyridamole (DIPY), (iii) 100 μM DIPY, and (iv) 1000 μM DIPY), were inserted in the vertebral bodies of 15 female sheep (weight ~65 kg). Qualitative and quantitative analysis were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…DIPY, an indirect adenosine agonist, is an extensively studied biologic compound [ 55 , 62 , 63 , 64 , 65 , 65 , 66 , 67 , 67 , 68 , 68 , 69 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. Historically, it has been used as a vasodilatory and antiplatelet agent [ 98 , 99 , 100 , 101 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…DIPY, an indirect adenosine agonist, is an extensively studied biologic compound [ 55 , 62 , 63 , 64 , 65 , 65 , 66 , 67 , 67 , 68 , 68 , 69 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. Historically, it has been used as a vasodilatory and antiplatelet agent [ 98 , 99 , 100 , 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other large animal models have studied different devices in different anatomical locations. Where, Pacheco-Vergara et al investigated the impact of DIPY on the osteointegration of titanium implants in sheep vertebrae [ 62 ]. It was found that DIPY-treated animals showed further bone integration and regeneration at 3 weeks post-operation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations